2015
DOI: 10.1063/1.4917378
|View full text |Cite
|
Sign up to set email alerts
|

Graphene photodetector integrated on silicon nitride waveguide

Abstract: We demonstrated a graphene photodetector integrated on silicon nitride waveguide. The photodetector worked in the photoconductor mode. The detection mechanisms of the device were based on photo-thermoelectric effect and bolometric effect. The waveguide absorption (0.025 dB/μm) with a chemical vapor deposition grown monolayer graphene on top was studied experimentally. The measurement agreed well with the simulation result. The Fermi level of the top layer graphene in the photodetector was analyzed by using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
0
37
1
Order By: Relevance
“…For SiN-based PICs, silicon can potentially be used for integrated photodiodes for visible/near-IR wavelengths. At telecom wavelengths, a first graphene-based photo-detector has been reported for SiNbased PICs [109]. To overcome this lack of high speed photodiode in SiN, it can be combined with SOI whereby there is access to high speed germanium photodiodes [80].…”
Section: F Pockels Effect and High-speed Functionsmentioning
confidence: 99%
“…For SiN-based PICs, silicon can potentially be used for integrated photodiodes for visible/near-IR wavelengths. At telecom wavelengths, a first graphene-based photo-detector has been reported for SiNbased PICs [109]. To overcome this lack of high speed photodiode in SiN, it can be combined with SOI whereby there is access to high speed germanium photodiodes [80].…”
Section: F Pockels Effect and High-speed Functionsmentioning
confidence: 99%
“…performance photodetectors) cannot be grown, leaving graphene as the currently only SiN-compatible material that has the potential to enable high-speed photodetection [9].…”
mentioning
confidence: 99%
“…For example, silicon nitride is a large bandgap (∼5 eV) deposited material that is compatible with CMOS fabrication technology. Wang et al [56] demonstrated the broadband graphene photodetector integrated on the silicon nitride waveguide. The two electrodes were set asymmetrically along the waveguide.…”
Section: Waveguide-integrated Graphene Photodetectorsmentioning
confidence: 99%